Indonesian-English Code-Mixing in Platform X Posts: Linguistic Levels and Communicative Functions - Maisa Salma Fauziyah; Otong Setiawan Djuharie (Journal of Education, Linguistics, Literature and Language Teaching, 2026)
This study examines the linguistic levels and communicative functions of Indonesian-English code-mixing in public posts on Platform X. Using a qualitative descriptive design and a sociolinguistic approach, it analyzes ten posts purposively collected from late 2025 to early 2026. Each post was coded by identifying the Indonesian matrix frame, classifying the English material as lexical, short phrasal, extended phrasal or clausal, or morphologically hybrid, and interpreting its primary communicative function from the textual and interactional context. The analysis shows that Indonesian remains the matrix language, while English operates as an embedded communicative resource. Lexical and short phrasal insertions are prominent, although several posts contain longer English stretches and one hybrid form combining an English stem with Indonesian morphology. The main functions are referential precision, expressive or emphatic stance, identity positioning, humor or irony, and phatic alignment. Because these functions can overlap, the analysis assigns a primary function according to the most immediate discourse effect and records secondary functions where relevant. The findings support an insertional and continuum-based account of code-mixing and indicate that Platform X enables locally grounded messages to incorporate globally recognizable linguistic resources. The study contributes a transparent coding framework for small-scale digital sociolinguistic analysis while acknowledging the limitations of corpus size and contextual access.